Effects of two staffing decisions on the performance of MNC subsidiaries. Issue 1 (3rd June 2014) - Ando, Naoki; Paik, Yongsun
Abstract : Purpose: – The purpose of this paper is to examine the relationship between foreign subsidiary staffing and subsidiary performance by focussing on two staffing practices: first, the ratio of parent country nationals (PCNs) to foreign subsidiary employees and second, the number of PCNs assigned to the foreign subsidiary. Design/methodology/approach: – Hypotheses predicting curvilinear relationships between the assignment of PCNs and subsidiary performance are tested using a panel data set consisting of 4, 858 foreign subsidiaries of Japanese multinational corporations (MNCs). Findings: – The results demonstrate that the two staffing practices have different effects on subsidiary performance. The ratio of PCNs to foreign subsidiary employees has an inverted U-shaped relationship with subsidiary performance, while the number of PCNs assigned to the subsidiary has a linear and negative effect on subsidiary performance. Research limitations/implications: – The results of this study are subject to limitations. First, the sample used in this study consists solely of the foreign subsidiaries of Japanese firms. This research design limits the generalizability of the findings of this study. Second, other decisions related to subsidiary staffing such as the ratio of PCNs in the subsidiary's top management team need to be examined to advance understandings of the relationship between subsidiary staffing and subsidiary performance. Practical implications: – MNCs need to identify the appropriate number of PCNs at which they can achieve the optimal trade-off with the PCN ratio to enhance the competitiveness and the performance of a foreign subsidiary. In doing so, they need to take into consideration that an increase in the number of PCNs has an immediate negative effect on the workplace morale of host country nationals. Originality/value: – This study incorporates two staffing practices into its analyses and shows that they have different implications for subsidiary performance. The results suggest that focussing on one staffing practice alone limits understanding of the complex relationship between foreign subsidiary staffing and subsidiary performance.